Legal Comparison of Deferred Prosecution Agreement (DPA) Methods in the USA, UK and Indonesia for Recovering State Financial Losses Due to Corruption Crimes - Pratama, Ilham Nur (Corruptio, 2023)
A deferred prosecution agreement (DPA) is an attempt to delay prosecution by making an agreement between the prosecutor and the corporation that committed the crime. This system has been implemented in the United Kingdom and the United States. DPA is one of the solutions to problems in the process of eradicating corruption. However, differences in the legal system are obstacles to its application in Indonesia. So it is necessary to develop an approach to be able to determine a model that is in accordance with the existing laws in Indonesia. Using normative juridical methods, how do DPA in USA, UK, and similar legal institutions compare with DPAs in Indonesia and their obstacles. Based on the research findings and discussions, it can be concluded that in the USA, DPA can be executed when there is corporate acknowledgment of criminal facts, an agreement to cooperate, a specified timeframe for the agreement, and an agreement involving a certain amount of monetary payments as a condition. In the UK, DPA serves as a probation for corporations, involving a negotiation, approval, and enforcement process. Furthermore, because Indonesia has not yet implemented DPA, but there are legal mechanisms with characteristics similar to DPA, namely diversion, restorative justice, the prosecutor's principle of opportunity, fines payment, and the MSAA/MRNIA model applied in the case of the Bank Indonesia Liquidity Assistance.